ATURAN SUBSIDI DALAM AGREEMENT ON FISHERIES SUBSIDIES TERHADAP PERIKANAN DI INDONESIA - Rahmih Yunisyah Mawaddah (Program Studi Ilmu Hukum Universtitas Muhammadiyah Gorontalo, 2023)
Fisheries subsidies are regulated in an agreement that takes effect in June 2022, namely the Agreement on Fisheries Subsidies, which regulates the prohibition of subsidies and their exceptions. With the formulation of the problem, namely how are the rules of subsidies in the agreement on fisheries subsidies? and what is the impact of the agreement on fisheries subsidies on fisheries in Indonesia. Using normative research method with qualitative analysis. The results show that the agreement on fisheries subsidies prohibits fisheries subsidies that contribute to IUU fishing, overfished stocks and allows fisheries subsidies in the event of a disaster with certain conditions. The impact of the agreement has resulted in Indonesian fishermen, most of whose main livelihoods are traditional fishermen and small-scale fishers, finding it difficult to get subsidies due to the prohibition where the subsidies are needed to support and help their communities.